Identifying the characteristics of nurse opinion leaders to aid the integration of genetics in nursing practice. (28th April 2014) - Andrews, Verity; Tonkin, Emma; Lancastle, Deborah; Kirk, Maggie
Abstract: Aim: To identify the characteristics of nurses opinion leaders in the context of genetics in health care and consider the findings for the integration of genetics in nursing practice. Background: Nurses need a basic understanding of the role genetics plays in their practice and about how best to support patients using genetic knowledge. Opinion leaders have been used previously to incorporate change initiatives and increase educational application. Identifying the characteristics of nurse opinion leaders may aid the engagement and continued integration of genetics into nursing practice. Design: A primarily quantitative approach over two phases, using online surveys conducted during 2011. Method: This article focuses on Phase 2 of a wider study. Oncology and primary care nurses were surveyed to identify the characteristics and demographic indicators of nurse opinion leaders. Tests for data normality followed by the suitable test for group comparison was applied with significance level set at <0·05. Results: Nineteen respondents ( n = 19/88; 21·6%) were categorized as opinion leaders and two subgroups were identified: Genetic Opinion Leaders and Opinion Leaders with an Interest in Genetics. Seven characteristics were deemed statistically significant (Mann–Whitney, Chi‐Square, t ‐test) in identifying nurse opinion leaders, including being open to experience and having a perceived level of influence over others. Conclusion: The identified characteristics could be used to enhance the integration of genetics into nursing practice through the use of opinion leaders. Further thought needs to be given to the refinement of the identified characteristics and to the use of such a unique group of nurses.